Modeling the process of deodorization of cottonseed oil in a liquid-vapor-floating nozzle system - Xamdamov Anvar Maxmudovich; Naziraliyeva Nigora Jo’ramirza qizi (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
There is a high growth in global demand for consumer oils, including soybean, palm, sunflower, rapeseed, and cottonseed oils. In order to increase the production of deodorized oil, a number of measures are currently being implemented in our republic to improve vegetable oil production technologies, comprehensively process oil-bearing vegetable raw materials, and re-equip oil and fat enterprises with modern technologies and high-tech efficient equipment. The development strategy of the new Uzbekistan sets such tasks as "implementing the food industry development program to increase the volume of food products to 7.4 million tons by 2026, and the assortment of food products from 898 to 1,100..." Accordingly, scientific research aimed at improving the deodorization process using nozzles based on a computer model is of urgent importance in increasing the efficiency of producing high-quality vegetable oil.